A comparison of the Hungarian mangalitza and dutch organic pork chains - Pocsai, Krisztina (Applied Studies in Agribusiness and Commerce, 2012)
The aim of this paper is to present the Hungarian mangalitza pig and Dutch organic pig supply chains and, in interrogating the differences between the two sectors, to make suggestions for the efficient operation of the Hungarian mangalitza breeding sector. The information about the two was sourced by a depth interview and literature reviews. It is established that there are few similarities between the two segments. In both sectors, the pigs are kept outdoors in large paddocks, there are also National Associations: in Hungary, the Association of Mangalitza Breeders (NAMB), in The Netherlands, the Organic Pork Growers. They hold a general meeting every year, where they discuss issues such as volume, quality, price, marketing and the future challenges and opportunities. There is strong demand both for the mangalitza and also for Dutch organic pork products on foreign markets. The main difference between them is their information systems. In The Netherlands, information flows via FarmingNet, but in the mangalitza sector, no such system exists. Yet, such a system would represent a breaking point for the adequate flow of data and efficient production for the NAMB, because then, Hungarian farmers would be forced to supply data.